Fatores psicossociais associados ao presenteísmo e a perda de produtividade em trabalhadores de enfermagem - Sousa, Raymara Melo de (2022)
Introduction: Presenteeism isrelated to the behavior of the individual who keeps working even though he has some poor health condition. The literature shows that this phenomenon is related to psychosocial factors, such as common mental disorders and the Burnout Syndrome, which has been gaining importance in the organizational context due to the precarious working conditions. In this sense, the nursing work stands out, a category that already faces worrying challenges, which together with the aforementioned problems and phenomena, can trigger negative outcomes to the worker's health and the consequent adoption of presenteeists practices. Objectives: To analyze the psychosocial factors associated with presenteeism and loss of productivity in nursing workers. Methods: Cross-sectional, analytical study, with 291 nursing professionals from a Municipal Hospital and Emergency Room. Data collection occurred between October 2019 and January 2020, through the self-applied instruments: 1-) sociodemographic characterization, work and health conditions, 2-) Maslach Burnout Inventory - Human Services Survey, 3-) Self Reporting Questionnaire-20, 4-) Standford Presenteeism Scale and 5-) Work Limitations Questionnaire. The data were analyzed by the R software, descriptive and inferential statistics and by Mann-Whitney, Kruskal Wallis and logistic regression tests, respecting the significance level of 5%. This study emerged from a matrix project approved by the Ethics in Research Committee of the University with opinion 3.217.476, where the recommendations for research with human beings were met, with authorization previously granted for the use of the instruments, as well as the license for the Maslach Burnout Inventory duly acquired from Mind Garden. Results: Temporary professionals, in critical and emergency sectors, working the night shift and diagnosed with gastritis were associated with loss of productivity. Workers with children, migraine headache, anxiety, depression and a history of sick leave were associated with presenteeism. Problems with gastritis, anxiety associated with depression, double vincule, alcohol consumption and smoking were associated with higher risks of Burnout Syndrome. High levels of emotional exhaustion and depersonalization, low professional achievement and Burnout Syndrome were associated with a loss of productivity. On the other hand, leisure practice proved to be a protective factor for the phenomena investigated. The occurrence of mental disorders was associated with presenteeism and a loss of productivity, with impairment to the general index and to the mental/interpersonal and production domains. Conclusion: Burnout Syndrome was associated with work and health aspects and with a loss of productivity. The occurrence of mental disorders presented chances for presenteeism and limitations in the productive capacity. Understanding this picture of the strong influence of the work context, identifying the Burnout Syndrome and the tendency to develop it, investigating presenteeism and productivity from different perspectives are relevant data about the health of these workers. Therefore, cultivating a broad and critical look at the nursing context can contribute to foster strategies and minimizing such deleterious effects, thus promoting healthy working conditions for this category.